Detection of voluntary dehydration in paediatric populations using non‐invasive point‐of‐care saliva and urine testing. (29th December 2020) - Faidah, Nur; Soraya, Gita V; Erlichster, Michael; Natzir, Rosdiana; Chana, Gursharan; Skafidas, Efstratios; Hardjo, Marhaen; Ganda, Idham J; Bahar, Burhanuddin
Abstract : Aim: Voluntary dehydration, or lack of fluid intake despite water availability, is common in otherwise healthy children, and can lead to adverse effects. Most dehydration biomarkers are impractical for routine assessment in paediatric populations. This study aimed to assess two non‐invasive hydration assessment tools, urine specific gravity (USG ) and a novel point‐of‐care (POC) salivary osmolarity (SOSM) sensor, in healthy children. Methods: Volunteers were tested by colorimetric USG and a handheld SOSM system. Observed values were compared against previous studies to determine hydration status, as was the concordance between parameters. Results: At the common USG threshold of 1.020, 42.4% of the 139 healthy children were dehydrated. The same prevalence was found using the 70‐mOSM cut‐off value. Comparative analysis of SOSM at varying USG thresholds demonstrated significantly higher SOSM in dehydrated children with a USG ≥ 1.030 ( P = 0.002). Conclusion: At the USG threshold of 1.020 and SOSM threshold of 70 mOSM, 42.4% of healthy children were found to be voluntarily dehydrated. Significantly higher SOSM was observed in dehydrated children (USG ≥ 1.030). As the first study on the utility of POC SOSM measurements for detecting dehydration, these results provide a foundation for future POC characterisation of SOSM in other populations and clinical contexts.